2022
DOI: 10.1063/5.0092833
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/SOI-based self-powered Schottky barrier photodiode array

Abstract: We have fabricated a four-element graphene/silicon on insulator (SOI) based Schottky barrier photodiode array (PDA) and investigated its optoelectronic device performance. In our device design, monolayer graphene is utilized as a common electrode on a lithographically defined linear array of n-type Si channels on a SOI substrate. As revealed by wavelength resolved photocurrent spectroscopy measurements, each element in the PDA structure exhibited a maximum spectral responsivity of around 0.1 A/W under a self-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…Considering the Schottky-Mott model, where Φ B is defined as the difference between the work function of graphene (W G ) and the electron affinity of Si (χ Si = 4.05 eV), W G was calculated as ~4.86 eV in average for PD elements, respectively. These two diode parameters are consistent with our previous work [18] and those of G/n-Si based Schottky barrier photodiodes fabricated on thick n-Si substrates [26].…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Considering the Schottky-Mott model, where Φ B is defined as the difference between the work function of graphene (W G ) and the electron affinity of Si (χ Si = 4.05 eV), W G was calculated as ~4.86 eV in average for PD elements, respectively. These two diode parameters are consistent with our previous work [18] and those of G/n-Si based Schottky barrier photodiodes fabricated on thick n-Si substrates [26].…”
Section: Resultssupporting
confidence: 91%
“…Contrary to previous studies based on the fabrication of single pixel G/n-Si Schottky devices with different architectures [15][16][17], our previous work showed that monolayer graphene can be utilized as a common electrode on a lithographically defined as linearly four channel n-type Si arrays on a SOI substrate [18]. In order to further minimize the possible optical crosstalk between elements and hence decrease the dark current in junction, it has become important to separate and disconnected individual graphene electrodes on every single Si element in the array and examine the device performances.…”
Section: Introductioncontrasting
confidence: 62%
See 3 more Smart Citations